Randomized trial of simplified LV5FU2 versus FOLFOX7 followed by FOLFIRI (MIROX) in patients with initially resectable metastatic colorectal cancer: a GERCOR study. (1st April 2013) - Hebbar, Mohamed; Chibaudel, Benoist; André, Thierry; Louvet, Christophe; Smith, Denis; Mineur, Laurent; Bennamoun, Mostepha; Mabro, May; Brusquant, David; Bonnetain, Franck; Pruvot, François-René; de Gramont, Aimery
<x xml:space="preserve">Abstract</x> Objectives: To evaluate the MIROX strategy (6 FOLFOX7 cycles followed by 6 FOLFIRI cycles) in patients with resected or resectable metastases from colorectal cancer. Methods: This trial compared the MIROX strategy to 12 cycles of simplified LV5FU2 (sLV5FU2). Chemotherapy was perioperative or adjuvant, at the investigator's decision, with stratification for this parameter. The primary objective was disease-free survival (DFS). The trial was interrupted in 2004, following the results of the adjuvant MOSAIC trial showing superiority of FOLFOX4 over LV5FU2. Results: Thirty-nine patients were included: 20 in MIROX arm and 19 in sLV5FU2 arm. Median DFS was higher in the MIROX arm (not reached versus 24·8 months, P = 0·044). MIROX regimen was well tolerated; 5/20 patients experienced a Grade 3 sensoryneuropathy. Conclusion: The MIROX strategy demonstrated promising efficacy, but this must be considered cautiously due to the small number of patients included. The pragmatic approach adopted for the treatment chronology is feasible.